Identifying appropriate land-use mix measures for use in a national walkability index - Suzanne Mavoa; Serryn Eagleson; Hannah M Badland; Lucy Gunn; Claire Boulange; Joshua Stewart; Billie Giles-Corti (Journal of Transport and Land Use, 2018)
Walkability indices can guide planning and policy for more sustainable and liveble cities. Land-use mix is an important component of walkability that can be measured in a number of ways. Many land-use mix measures require fine-scaled land-use data that are not always available, especially when analyzing walkability across larger geographic extents. This study investigated the feasibility of calculating a national walkability index in Australia, using metropolitan Melbourne as a case study. The study focused on the dual challenges of selecting an appropriate measure of land-use mix and identifying an appropriate land-use data source. We calculated an entropy land-use mix measure with three different Australian land-use datasets. Our comparison of the resulting land-use mix measures highlighted the differences in the land-use datasets and led to our conclusion that none of the three land-use datasets was appropriate for use in a national land-use mix measure. Therefore, we also developed two new exploratory “intensity” measures of land use — daily living and local living — that were able to be calculated nationally with readily available data. Modelled associations with transport walking and comparisons with the entropy land-use mix measures indicate that these new measures were appropriate for assessing national land use in a national walkability index.